Optical and thermal studies of Nd3+ doped inorganic liquid medium for scalable laser source. (April 2022) - Varshney, A.K.; Mainuddin,; Kumar, Sanjeev; Kumar, Ashwani; Singhal, Gaurav; Gupta, Mohini; Vijaya Prakash, G.
Graphical abstract: Highlights: Discusses optical and thermal studies of laser diode pumped Nd 3+ doped inorganic liquid medium. Homogenous laser medium synthesized by mixing Nd 3+ ions in POCl3 solvent with Lewis acid SnCl4 . Peak absorption of the liquid medium occurs at 800 nm with peak emission at 1054 nm. Judd-Ofelt theory determines stimulated emission cross-section and quantum efficiency. FTIR studies show absence of O-H bonds which may impede lasing. Synthesized laser medium shows a loss coefficient <0.5 % cm −1 @1054nm. Modest pump intensities of ∼600 W/cm 2 with laminar flow are feasible. Abstract: The optical and thermal properties of Nd 3+ doped inorganic liquid medium are investigated for the development of a scalable laser source. The homogenous liquid medium is synthesized by mixing rare earth Nd 3+ ions in a POCl3 solvent host with Lewis acid SnCl4 . The optical studies are carried out to assess the lasing potential of the medium and to discern its absorption and emission spectra. The observed results show that peak absorption of the liquid medium occurs at 800 nm with peak emission at 1054 nm marginally blue-shifted as compared to corresponding ones in Nd:YAG single-crystal. Judd-Ofelt theory is successfully used to determine the stimulated emission cross-section and quantum yield of the synthesized liquid medium. Fourier Transform Infrared (FTIR) Spectroscopic studies reveal that the medium is free from hydrogen-containing species which may impede lasing. The synthesized liquid medium is transparent at lasing wavelength showing a transmission loss coefficient of less than 0.5 % cm −1 . Thermal studies of the synthesized liquid medium under high pump irradiance are performed both in sealed-off static as well as circulating liquid medium. This enables to identify the plausible configuration for lasing. It is observed that thermal-induced convection effects appearing in the sealed-off static medium can be mitigated by circulating the liquid medium. The liquid medium flows under a laminar regime at rates of 10–12 L per minute (lpm) below the critical Reynolds number. Hence, the characterization studies of Nd 3+ doped inorganic liquid medium are promising towards the development of scalable laser sources.